P41 Identifying anti-mitochondrial antibody (AMA) positive prevalence: An undiagnosed disease in North Yorkshire. (28th September 2020) - Jones, Kayleigh; Millson, Charles; Hutchinson, John; Turner, Lucy
Abstract : Introduction: Primary Biliary Cholangitis (PBC) is a chronic, progressive disorder, with a relatively well-tolerated treatment option in the form of Ursodeoxycholic acid. A confident diagnosis of PBC relies upon a positive anti-mitochondrial antibody (AMA), a raised alkaline phosphatase (ALP) and/or immunoglobulin M (IgM). York Teaching Hospitals NHS Foundation Trust (YTHT) serves a population of 800, 000 1, however our existing PBC database included only 100 patients. Given the prevalence (35 per 100, 000 2 ) it is likely there are a significant number of undiagnosed cases within our population. Aim: To review historical positive AMA tests throughout YTHT, with the aim of identifying patients with hitherto undiagnosed PBC. Method: An IT-based search identified all positive AMA blood tests over a nine year period (2009–2018) (n = 731). An electronic note review of a proportion (n = 204) established demographic details, blood test results (including liver blood tests and immunoglobulins), the department requesting the test and consequential action taken. Results: Data from 2017–18 revealed 204 patients with a positive AMA, 88% of whom were female. Tests were predominantly requested by specialties other than hepatology; secondary care specialties (52%) GPs (38%) and hepatologists (9%). 34% had a known diagnosis of PBC. 31% of the cohort had a raised ALP (ALP >130 IU/L). Of those patients in whom immunoglobulins were performed (n = 112) over half, 57%, had a positive IgM. 115 patients (56%) had a positive AMA only, of these hepatology advice was sought in less than half (44%) of cases. 19 patients (9%) had results in keeping with a diagnosis of PBC, but were not referred, or previously known to, the hepatology service. Discussion: Our results have identified a significant number of patients in this population with undiagnosed PBC who could benefit from treatment. Identifying patients who potentially have established PBC is relatively non-invasive, and form part of the panel of blood tests frequently requested in primary and secondary care. As many such patients do not end up with either a formal diagnosis or appropriate referral, perhaps it is time to recommend all hospitals interrogate their laboratory databases in this way. Reference: www.yorkhospitals.nhs.uk/about-us/ Hirschfield GM, Dyson JK, Alexander GJM, et al . The British Society of Gastroenterology/UK-PBC primary biliary cholangitis treatment and management guidelines. Gut 2018;67 :1568–1594